Towards a Neurobehavioral Profile of Fetal Alcohol Spectrum Disorders - Mattson, Sarah N. (2010)
BACKGROUND: A primary goal of recent research is the development of neurobehavioral profiles that specifically define fetal alcohol spectrum disorders (FASD), which may assist differential diagnosis or improve treatment. In the current study we define a preliminary profile using neuropsychological data from a multisite study. METHODS: Data were collected using a broad neurobehavioral protocol from two sites of a multisite study of FASD. Subjects were children with heavy prenatal alcohol exposure and unexposed controls. The alcohol-exposed group included children with and with out fetal alcohol syndrome (FAS). From 547 neuropsychological, 22 variables were selected for analysis based on their ability to distinguish children with heavy prenatal alcohol exposure from nonexposed controls. These data were analyzed using latent profile analysis (LPA). RESULTS: The results indicated that a 2-class model best fit the data. The resulting profile was successful at distinguishing subjects with FAS from nonexposed controls without FAS with 92% overall accuracy; 87.8% of FAS cases and 95.7% of controls were correctly classified. The same analysis was repeated with children with heavy prenatal alcohol exposure but without FAS and non-exposed controls with similar results. The overall accuracy was 84.7%; 68.4% of alcohol-exposed cases and 95% of controls were correctly classified. In both analyses, the profile based on neuropsychological variables was more successful at distinguishing the groups than was IQ alone. CONCLUSIONS: We used data from two sites of a multisite study and a broad neuropsychological test battery to determine a profile that could be used to accurately identify children affected by prenatal alcohol exposure. Results indicated that measures of executive function and spatial processing are especially sensitive to prenatal alcohol exposure.